Prevalence of Helicobacter pylori Infection by Birth Year and Geographic Area in Japan. Issue 2 (10th February 2014) - Ueda, Junko; Gosho, Masahiko; Inui, Yoshikatsu; Matsuda, Toru; Sakakibara, Masatoshi; Mabe, Katsuhiro; Nakajima, Shigemi; Shimoyama, Tadashi; Yasuda, Mitsugi; Kawai, Takashi; Murakami, Kazunari; Kamada, Tomoari; et al.
Abstract Background Helicobacter pylori (H. pylori)‐related diseases are responsible for a tremendous amount of morbidity and mortality in Japan. We estimated the prevalence of H. pylori infection by sex, birth year, and geographic area among Japanese adults. Materials and Methods This cross‐sectional study included 14, 716 subjects aged 20 years or more who underwent a health checkup between May 1997 and March 2013 in seven geographic areas throughout Japan. Relevant information on the demographics and status of H. pylori infection was retrieved from the electronic database. The univariate log‐binominal regression model was used to estimate the prevalence of H. pylori infection, taking birth year into consideration. The multivariate log‐binominal regression model was used to compare the prevalence of H. pylori infection between seven geographic areas. Results The overall prevalence of H. pylori infection was 37.6% in women and 43.2% in men. Among seven geographic areas, Hokkaido showed the lowest prevalence (29.4%), while Yamagata Prefecture represented the highest (54.5%). The prevalence of H. pylori infection was highest in the 1940–1949 birth cohort and then decreased in the ensuing birth cohorts; the risk ratio (RR) was 0.85 (95% confidence interval (CI) 0.84–0.87) for changes in the 10‐year birth cohort. Individuals in Yamagata Prefecture had the highest RR of acquiring H. pylori infection in all three birth cohorts (RR = 1.53 for 1940, RR = 1.69 for 1950, and RR = 1.85 for 1960) when compared with those in Hokkaido. Conclusions The prevalence of H. pylori infection increases with age and exhibits geographic variation in Japan. There has been a striking decrease in the prevalence of H. pylori infection, especially in younger Japanese populations.